Cystic tumour of the atrioventricular node: case report and literature review - Stephen D. Cohle (Oxford University Press, 2019)
Cystic tumour of the atrioventricular node is the smallest tumour that can cause sudden cardiac death. This lesion arises from foregut endodermal rests which become enfolded into the heart during embryogenesis. Typically causing heart block, the tumour can cause sudden death despite pacemaker placement. Sudden death in such cases can be caused by arrhythmogenic ectopic foci arising from impaired electrical impulse propagation through the abnormal atrioventricular junction conducting tissue.